2010
DOI: 10.1063/1.3290767
|View full text |Cite
|
Sign up to set email alerts
|

Error and efficiency of simulated tempering simulations

Abstract: We derive simple analytical expressions for the error and computational efficiency of simulated tempering ͑ST͒ simulations. The theory applies to the important case of systems whose dynamics at long times is dominated by the slow interconversion between two metastable states. An extension to the multistate case is described. We show that the relative gain in efficiency of ST simulations over regular molecular dynamics ͑MD͒ or Monte Carlo ͑MC͒ simulations is given by the ratio of their reactive fluxes, i.e., th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 35 publications
1
58
0
Order By: Relevance
“…As seen, while the T 1 ↔ T 2 transitions took place more often because the parameter f 2 was getting better, the T 2 → T 3 transitions were also attempted but all failed. At the step 7.95 × 10 5 , another large positive energy fluctuation occurred and the attempt T 2 → T 3 was successful, and this resulted in the new update for f 3 (Fig. 2(d)).…”
Section: Tem Consists Of 2 Non-interacting Particles Each Has the Pomentioning
confidence: 99%
See 1 more Smart Citation
“…As seen, while the T 1 ↔ T 2 transitions took place more often because the parameter f 2 was getting better, the T 2 → T 3 transitions were also attempted but all failed. At the step 7.95 × 10 5 , another large positive energy fluctuation occurred and the attempt T 2 → T 3 was successful, and this resulted in the new update for f 3 (Fig. 2(d)).…”
Section: Tem Consists Of 2 Non-interacting Particles Each Has the Pomentioning
confidence: 99%
“…To accelerate the sampling, there has been considerable progress in developing a new class of simulation methods, referred to as the generalized-ensemble algorithms. [1][2][3][4] One of widely used generalized-ensemble algorithms is simulated tempering (ST). 5,6 The basic idea is that by coupling low temperature simulations with high temperature ones, one hopes to transfer the improved sampling at the higher temperature to the lower temperature.…”
mentioning
confidence: 99%
“…In more recent years, considerable attention has been paid to the application of ST to biomolecular simulations [36][37][38] due to its better scaling property with system size and superior acceptance ratio for temperature transitions. Several comparison studies [39][40][41] revealed that ST with a properly chosen temperature weight exhibits faster diffusion in temperature space and a better sampling efficiency in comparison to the tREM. Combinations of the ST and other enhanced sampling methods have further explored this synergistic advantage.…”
Section: Introductionmentioning
confidence: 99%
“…45 A converged ST trajectory is essentially equivalent with a replica trajectory in an REMD simulation. Therefore, the following formula can be applied to the per replica data of the REMD simulations …”
mentioning
confidence: 99%